Becoming a Caterpillar: A Multimodal Perspective on Metamorphosis in Butoh Dance. Issue 1 (16th September 2021) - Esposito, Paola; Dziala, Dariusz
Butoh is a dance and somatic movement approach that emerged in Japan in the 1960s and today is practiced around the world. Due to its stylistic idiosyncrasies and lack of a formalised movement vocabulary, butoh is often referred to among its practitioners and in the literature as an indeterminate or 'formless' dance. While 'metamorphosis' has been recognised as butoh's core aesthetic trait (Fraleigh 2010 ;Baird and Candelario 2019 ), what this entails in practice has been little explored. This video article examines metamorphosis in butoh dance from a sensory anthropology perspective which attends to the micro-phenomenological dimensions of the practice. The author, a dancer-anthropologist, focuses on a practice of 'becoming a caterpillar' that she learnt at a butoh workshop given by Semimaru of the company Sankai Juku in London in 2014. Through a praxeography of selected exercises, integrated by a somatic or 'from the body' perspective (Farnell 1999 ), the author argues that the same techniques 'scaffold' (Downey 2004) metamorphosis by emphasising fluidity of bodily movement as well as the 'isolation' of body parts. Perceptual aspects of the practice are explored and reflected upon multimodally through a combination of textual, graphic, dance, and performance reenactments. Responding to ongoing debates on the value of integrating multimodality in anthropological research, practice and dissemination of scholarship, the article proposes that multimodality can extend the conceptual and methodological reach into experiential dimensions of bodily practice by foregrounding both sensory and imaginal aspects of doing. Drawing on anthropological studies of perception in ritual action, the video article argues that butoh metamorphosis relies on a principle of 'illusion' whereby a change in the dancer's kinetic organisation engenders a visual impression of their bodies transforming into something else. This metamorphic logic is by no means exclusive to butoh but is found in other styles of performance, including puppet theatre. Kapferer's (2004 ) notion of virtuality is mobilised here to highlight how the reconfiguring of perceptual patterns through performative action can effect transformation by means of 'modulating reality' and 'adjusting its dynamics'. As shown by the example of the caterpillar, in butoh dance the transformation is double: on the optical and imaginal level of the dancer's bodily form, as coinciding with a 'view from the outside', and on the somatic level of the practitioner's lived body as experienced 'from the inside'. It is further argued that a butoh dancer's propension to somatically relate to imaginal dimensions of the practice relies on the phenomenological principle of sensory reversibility, whereby tactility-kinaesthesia 'merges' with the sense of vision.